2004
DOI: 10.1007/s00213-004-2084-3
|View full text |Cite
|
Sign up to set email alerts
|

Cortical 3α-hydroxy-5α-pregnan-20-one levels after acute administration of Δ9-tetrahydrocannabinol, cocaine and morphine

Abstract: Some, but not all, drugs of abuse produce increases in cortical allopregnanolone levels. In addition, increases in plasma steroid precursor levels do not always translate into increases in brain allopregnanolone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Further, these findings suggest that physiological and/or interoceptive effects of cocaine may involve stress-induced increases in corticosteroids and progestins and that administration of P may dampen some of the psychotropic effects of cocaine by attenuating stress-induced activation of neuroendocrine responses. It is important to note that it has also been reported that cocaine has no effect on 3α,5α-THP levels (Grobin et al, 2005).…”
Section: Progestins and Response To Drugs Of Abusementioning
confidence: 92%
See 2 more Smart Citations
“…Further, these findings suggest that physiological and/or interoceptive effects of cocaine may involve stress-induced increases in corticosteroids and progestins and that administration of P may dampen some of the psychotropic effects of cocaine by attenuating stress-induced activation of neuroendocrine responses. It is important to note that it has also been reported that cocaine has no effect on 3α,5α-THP levels (Grobin et al, 2005).…”
Section: Progestins and Response To Drugs Of Abusementioning
confidence: 92%
“…Administration of various drugs of abuse has also been demonstrated to enhance production of 3α,5α-THP. For example, systemic administration of delta9-tetrahydrocannabinol can increase cortical levels of 3α,5α-THP (Grobin et al, 2005). High, but not lower, dosages of morphine also enhance cortical levels of 3α,5α-THP (Grobin et al, 2005) and 3α,5α-THP administration amplifies the release of dopamine in the nucleus accumbens in response to morphine (Rouge-Pont et al, 2002).…”
Section: Progestins Stress Hpa Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, examination stress (Droogleever Fortuyn et al, 2004) and performance stress (Girdler et al, 2006) were also accompanied by significant elevations in circulating levels of THP in both sexes, although ethnic differences have been reported (Girdler et al, 2006). Recent studies also suggest that drugs such as alcohol (VanDoren et al, 2000), morphine and δ-9-tetrahydrocannabinol (Grobin et al, 2005) increase circulating THP levels as a long-term response to intake of these drugs. Thus, stress may represent an additional mechanism by which neurosteroid levels can be altered over time, irrespective of gender.…”
Section: Stress and Addictive Drugsmentioning
confidence: 99%
“…The neurosteroid pregnenolone has been shown to enhance memory when given intrathecally (Flood, et al, 1992,Flood, et al, 1995,Mathis, et al, 1994,Mayo, et al, 1993,Robel, et al, 1995. In rodent models of alcohol intoxication, one mechanism through which alcohol elicits its effects is through increased synthesis of allopregnanolone in the brain (Brot, et al, 1997,Caldeira, et al, 2004,Finn, et al, 2004,Finn, et al, 2003,Follesa, et al, 2004,Grobin, et al, 2005,Janis, et al, 1998,VanDoren, et al, 2000. Finally, the neurosteroid allopregnanolone has been implicated in a severe form of premenstrual disorder, called premenstrual dysphoric disorder (Backstrom, et al, 2003,Bernardi, et al, 2004,Bicikova, et al, 1998,Bixo, et al, 1997,Epperson, et al, 2002,Friedman, et al, 1993,Girdler, et al, 2001,Monteleone, et al, 2000,Rapkin, et al, 1997,Schmidt, et al, 1994,Smith, et al, 1998.…”
Section: Introductionmentioning
confidence: 99%